2001
DOI: 10.1152/ajpheart.2001.281.6.h2410
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol-induced cardiac hypertrophy: role of circulatory versus cardiac renin-angiotensin system

Abstract: To assess the possible contribution of the circulatory and cardiac renin-angiotensin system (RAS) to the cardiac hypertrophy induced by a beta-agonist, the present study evaluated the effects of isoproterenol, alone or combined with an angiotensin I-converting enzyme inhibitor or AT(1) receptor blocker, on plasma and LV renin activity, ANG I, and ANG II, as well as left ventricular (LV) and right ventricular (RV) weight. Male Wistar rats received isoproterenol by osmotic minipump subcutaneously and quinapril o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 17 publications
9
90
0
Order By: Relevance
“…This feature is consistent with the previous reports. [6][7][8]10,14,17) In the present study, telmisartan had no influence on the isoprenalineinduced myocardial fibrosis. Leenen et al reported that losartan increased the isoprenaline-induced LV fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…This feature is consistent with the previous reports. [6][7][8]10,14,17) In the present study, telmisartan had no influence on the isoprenalineinduced myocardial fibrosis. Leenen et al reported that losartan increased the isoprenaline-induced LV fibrosis.…”
Section: Discussionmentioning
confidence: 80%
“…As described previously (27), plasma ANG II concentration was measured by RIA after extraction on C18 Sep-Pak cartridges and separation by HPLC, and PRA was determined by RIA to measure the ANG I generated during incubation at 37°C for 1 h.…”
Section: Protocol 2: Intracerebroventricular Na ϩ -Rich Acsf and Braimentioning
confidence: 99%
“…Surprisingly, ISO treatment induced an increase in blood pressure ( Figure 4B), although this has been shown previously with catecholamine administration. 3,14 The substantial increase in heart rate elicited by chronic treatment with this Gs-coupled receptor agonist (untreated mice, 242Ϯ22 bpm; ISO-treated mice, 577Ϯ29 bpm) likely mediates a mechanical mechanism to increase blood pressure and override the vasodilatory signals of the ligand. The hyperten- …”
Section: Cardiac and Hemodynamic Responses To Chronic Gs-coupled Recementioning
confidence: 99%
“…Additionally, ISO administration, which acts via the Gs-coupled ␤AR, has been shown to activate the Gq-coupled circulatory renin-angiotensin system. 14 To delineate the contribution of Gq signaling in the vasculature and heart to the development of cardiac hypertrophy, after exposure to Gq-coupled receptor agonists, we have developed a line of transgenic mice that express the GqI exclusively in VSM cells under the control of the SM22␣ promoter. Herein, we describe the physiological implications of inhibiting Gq-signal transduction specifically in either the vasculature or myocardium, and determine its impact on blood pressure and cardiac hypertrophy.…”
mentioning
confidence: 99%